The sacred fatwa of efficient defense and its role in promoting social cohesion and building peace in Iraqi society (an analytical study with a sociological perspective) - جابر, سارة علي; غزوان, انس عباس (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The religious authority, represented by the supreme authority, Sayyed al-Sistani, “may his life be long” believes that social cohesion is what achieves societal peace, rapprochement, and solidarity, and strengthens relations between members of society, and it is not possible to achieve lasting, continuous peace unless it is based on a strong and established base, which is building peace and cohesion first within the state between Its components, because building global peace, preserving the sovereignty of the state, its land and its people, and preserving it from any external aggression depends essentially on the fact that the state actually lives in peace within it and believes in peaceful coexistence. The religious authority’s interest in promoting and protecting human rights and fundamental freedoms emerges from its conviction of the inherent dignity that humanity represents. And inalienable rights. Preserving security and societal peace and achieving social cohesion are among the most important goals of the religious authority. Indeed, it is the focus of the speeches of His Eminence Sayyid al-Sistani, may his soul be long lasted. It is also the impetus for issuing the sacred fatwa of the Competent Defense. The role of the religious authority in the field of achieving social cohesion and building peace has become a basic pillar and one of the most important goals of the religious authority. Through its curricula, it can build lasting peace among members of society, regardless of differences in races, ideologies, beliefs, sects, and nationalities.